Behaviour Changes of Elementary School Students Who Had Menarche and Educational Program Needed Relating to Menarche - Aris Nurkhamidi; Agus Khumaedy; Siti Khuzaiyah (Universitas Islam Negeri K.H. Abdurrahman Wahid Pekalongan, 2023)
Menarche marks a critical transition in a girl's life, signaling the onset of biological and reproductive maturity, and, from a fiqh perspective, the entry into the mukallaf stage of religious responsibility. However, this biological milestone is accompanied by significant physical, emotional, and social changes that necessitate appropriate educational interventions. This qualitative study aimed to explore behavioral changes observed in elementary school students following menarche and to identify educational programs needed to support their development. Data were collected through teacher interviews and focus group discussions across six elementary schools in Pekalongan City, Central Java, Indonesia, and analyzed using thematic content analysis. Findings revealed that post-menarche students exhibited increased attention-seeking behaviors towards the opposite sex, heightened self-focus on physical appearance, and active engagement on social media. However, schools lacked targeted educational programs addressing menstruation, reproductive health, and emotional development. This study emphasizes the urgent need for structured educational and counseling programs that integrate biological, psychological, and religious dimensions to support students during menarche, promoting healthy development and well-being. Collaborative efforts between schools, health departments, and educational authorities are recommended to ensure holistic student support.